Random discounted expected utility - Jose Apesteguia; Miguel A. Ballester; Ángelo Gutiérrez-Daza (Banco de México, 2024)
This paper introduces the random discounted expected utility (RDEU) model, which we have developed as a means to deal with heterogeneous risk and time preferences. The RDEU model provides an explicit linkage between preference and choice heterogeneity. We prove it has solid comparative statics, discuss its identification, and demonstrate its computational convenience. Finally, we use two distinct experimental datasets to illustrate the advantages of the RDEU model over common alternatives for estimating heterogeneity in preferences across individuals.
Keywords: C01; D01; 330; Heterogeneity; Risk Preferences; Time Preferences; Comparative Statics; Random Utility Models